131k views
0 votes
What is the translation rule for this translation?

Question 2 options:

T(x, y) -> (x -6, y-3)


T(x, y) -> (x-3, y-6)


T(x, y) -> (x+6, y+3)


T(x, y) -> (x+3, y+6)

What is the translation rule for this translation? Question 2 options: T(x, y) -&gt-example-1
User Mr Bean
by
5.1k points

1 Answer

6 votes

Answer:

T(x,y)->(x-3,y-6)

Explanation:

Say we take point E and E1. To move E to E1, we need to move it to the left 3 units, already giving us x-3. Then, we need to find out how far down it moved. by counting the units, we can tell that it moved 6 units down as well, giving us y-6. In the end, we get T(x,y)->(x-3,y-6).

User Sahle
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.